CHRONIC KIDNEY DISEASE OF UNKNOWN AETIOLOGY OF SRI LANKA IN HUMAN RIGHT PERSPECTIVE: WITH SPECIAL REFERENCE TO NATIONAL AND INTERNATIONAL HUMAN RIGHTS REGIME (Proceedings of the International Conference on Social Sciences, 2018)
Chronic Kidney Disease of Unknown Aetiology (CKDu) is a condition that the reduction of the kidney functions over a period of time. CKDu has affected the dry zone in Sri Lanka and last few decades the use of agro-chemicals rising up in these areas due to large-scale cultivation of paddy crop. The researchers revealed that the accumulation of heavy metals as agro-chemical residues in water resources is one of the major environmental factors affect the CKDu. At present, United Nations recognizes the right to access clean water as a human right, even though the people of dry zone unable to enjoy the right due to pollution of their water resources by agro-chemical residues. Further, their right to life, right to a healthy environment and the right to engage in lawful occupation also violate due to this disease. The main purpose of this research is to identify the international and national human right provisions relate to CKDu in Sri Lanka. This research mainly explores the contribution of national and international jurisdiction to eradicate or minimize the outbreak of CKDu from Sri Lanka while ensuring the fundamental rights of citizens.
Keywords: Chronic Kidney Disease of Unknown Aetiology; Fundamental Rights; Constitution of Sri Lanka; International Human Right Law